2021
DOI: 10.1111/cod.13826
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy and allergic contact dermatitis from benzalkonium chloride in a tertiary dermatology center in Melbourne, Australia

Abstract: BackgroundBenzalkonium chloride (BAK) is a quaternary ammonium compound that is used widely as an antiseptic and preservative. It is a strong irritant and considered a weak sensitizer.ObjectiveTo analyze the temporal trend of BAK sensitization and the demographics of sensitized patients.MethodsWe conducted a single‐center retrospective study of 7390 patients who were patch tested with BAK between January 1, 2003 and December 31, 2019.ResultsOf the 7390 patients who were patch tested to BAK, 108 (1.5%) had a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…2,3 Nevertheless, these quaternary ammonium compounds, as well as PHMB, may cause clinically relevant contact allergy, and all three can also cause immediate-type hypersensitivity. 2,3,[6][7][8][9] The present case illustrates the contact allergenic nature of BAC and DDAC, and underlines the usefulness of using dilution series to demonstrate this. Moreover, it appears that DDAC and BAC are perhaps best patch tested in a pet.-and aq.-based vehicle, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…2,3 Nevertheless, these quaternary ammonium compounds, as well as PHMB, may cause clinically relevant contact allergy, and all three can also cause immediate-type hypersensitivity. 2,3,[6][7][8][9] The present case illustrates the contact allergenic nature of BAC and DDAC, and underlines the usefulness of using dilution series to demonstrate this. Moreover, it appears that DDAC and BAC are perhaps best patch tested in a pet.-and aq.-based vehicle, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…Being notorious skin irritants, the interpretation of patch test reactions to DDAC and BAC can be difficult, and false‐positive patch test reactions might occur 2,3 . Nevertheless, these quaternary ammonium compounds, as well as PHMB, may cause clinically relevant contact allergy, and all three can also cause immediate‐type hypersensitivity 2,3,6‐9 . The present case illustrates the contact allergenic nature of BAC and DDAC, and underlines the usefulness of using dilution series to demonstrate this.…”
Section: Discussionmentioning
confidence: 75%
“…This is probably because it is the most widespread QAC as preservative and antiseptic in medicines, cosmetics, and cleaning agents, but it might also be due to its intrinsic properties. A study of patients with contact allergy and CD found a trend to increase in BAC sensitization in the recent years, and the main sources of exposure were ophthalmic drops, topical antiseptics, and cosmetics ( Dear et al, 2021 ). Moreover, BAC was the sixth allergen giving the highest reaction within a large retrospective cohort of patch testing ( Veverka et al, 2018 ).…”
Section: Quaternary Ammonium Compounds-associated Delayed Hypersensit...mentioning
confidence: 99%
“…1 It is commonly found as an ingredient in personal care products, including deodorants, cosmetics, mouthwashes, ophthalmic solutions, and nasal sprays. 1 A 26-year-old Chinese woman was referred for recurrent erythematous patches with severe pruritus of 9 months' duration.The lesions began on the antecubital fossa, popliteal fossa, and abdomen and then rapidly spread to the entire body except the face and scalp. She was diagnosed with erythrodermic atopic dermatitis.…”
mentioning
confidence: 99%
“…1 It is commonly found as an ingredient in personal care products, including deodorants, cosmetics, mouthwashes, ophthalmic solutions, and nasal sprays. 1 A 26-year-old Chinese woman was referred for recurrent erythematous patches with severe pruritus of 9 months' duration.…”
mentioning
confidence: 99%